Surface Characteristics Comparison of Machining Waste Using Powder Metallurgy Method - Widianti, Ika Silviana; Raharjo, Yoga Kartiko; Safa'at, Ahmat; Suhariyanto, Suhariyanto; Nugroho, Giri (IPTEK The Journal of Engineering, 2025)
Machining processes generate metal waste in the form of fine powder that is often not reused efficiently. This study explores the potential reuse of metal machining waste powder through powder metallurgy, focusing on how sintering temperature affects mechanical properties and microstructure. Metal powder from ST60 steel machining was compacted and sintered at 1100°C, 1150°C, and 1200°C. The specimens were then compared to original ST60 steel. XRF analysis confirmed that iron was the dominant element in the waste powder. Microstructural analysis showed the presence of ferrite and pearlite in all specimens, with higher sintering temperatures increasing the ferrite content. In terms of mechanical performance, ST60 steel showed the highest hardness (80.6 HRB) and compressive strength (156.157 N/mm²). Among the specimens, the one sintered at 1100°C had the highest hardness (65.1 HRB) and compressive strength (73.293 N/mm²), closest to ST60 steel. The lowest surface roughness (7.058 Ra) was observed in the 1200°C specimen, approaching ST60’s value (2.003 Ra). These findings indicate that reused machining waste powder can be processed into useful products, especially for low-load applications, with optimal properties achieved at 1100°C sintering temperature.